Dynamic optimisation of the aeration in a small-size alternating activated sludge process - Fikar,M; Chachuat,B; Latifi,MA (2004)
This simulation study presents dynamic optimisation of a small size single basin wastewater treatment plant. The objectives are to determine an optimal sequence of aeration/non-aeration times and the corresponding periodical steady state subject to minimisation of energy consumption. Based on the optimal trajectories, two simple feedback rules are proposed that follow from properties of the optimal solution. Simulation results with these simple rules show very satisfactory control performance.